INTEGRATED MARKETING COMMUNICATION AND COFFEE SHOP CONSUMER PURCHASE DECISION IN SURAKARA CITY - Rivandi, Rachman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Integrated Marketing Communication is one of the new generation marketing approaches used by companies to focus their efforts more on acquiring, maintaining and developing relationships with customers and other stakeholders. The purpose of this study was to determine whether there is an effect of Integrated Marketing Communication on the stages of coffee shop consumer purchasing decisions in Surakara City. The population of this research is the people in Surakara who have done transactions at the "Dodolan Kopi" coffee shop. The number of respondents in this study was determined as many as 272 respondents who were selected using a non-probability sampling method with simple linear regression data analysis techniques. The independent variable tested in this study is Integrated Marketing Communication with dimensions of Advertising, Sales Promotion, Public Relations, Event & Experience, Direct Marketing, Interactive Marketing, Word of Mouth, and Personal Selling and the dependent variable is purchasing decisions. The results showed that the Integrated Marketing Communication variable had a positive effect on purchasing decisions. Furthermore, Public Relations is the dimension of Integrated Marketing Communication which is the most dominant and influences the consumer purchasing decisions of Dodolan Kopi